Securing small and medium-size businesses. Issue 7 (July 2016) - Mansfield-Devine, Steve
Abstract : It seems that barely a week goes by without the revelation that yet another large, high-profile organisation has been breached, with millions of records being stolen. It would be easy to imagine that hackers are attracted only by big-name firms with huge databases just begging to be ransacked. But as Colin Tankard, MD of Digital Pathways, points out in this interview, organisations of all sizes are at risk.